Strength measures are better than muscle mass measures in predicting health-related outcomes in older people: time to abandon the term sarcopenia?. Issue 1 (January 2017) - Menant, J.; Weber, F.; Lo, J.; Sturnieks, D.; Close, J.; Sachdev, P.; Brodaty, H.; Lord, S.
Abstract Summary There is no clear consensus on definition, cut-points or standardised assessments of sarcopenia. We found a lower limb strength assessment was at least as effective in predicting balance, mobility and falls in 419 older people as muscle mass-based measures of sarcopenia. Introduction There is currently no consensus on the definition, cut-points or standardised assessments of sarcopenia. This study aimed to investigate whether several published definitions of sarcopenia differentiate between older people with respect to important functional and health outcomes. Methods Four hundred nineteen community-living older adults (mean age 81.2 ± 4.5, 49 % female) completed assessments of body composition (dual-energy X-ray absorptiometry), strength, balance, mobility and disability. Falls were recorded prospectively for a year using monthly calendars. Sarcopenia was defined according to four skeletal mass-based definitions, two strength-based definitions (handgrip or knee extensor force) and a consensus algorithm (low mass and low strength or slow gait speed). Obesity was defined according to percentage fat mass or waist circumference. Results The four skeletal mass-based definitions varied considerably with respect to the percentage of participants classified as sarcopenic and their predictive accuracy for functional and health outcomes. The knee extension strength-based definition was equivalent to or better than the mass-based and consensus algorithm definitions; i.e. weaker participants performed poorly in tests of leaning balance, stepping reaction time, gait speed and mobility. They also had higher physiological fall risk scores and were 43 % more likely to fall at home than their stronger counterparts. Adding obesity to sarcopenia definitions identified participants with greater self-reported disability. Conclusions A simple lower limb strength assessment was at least as effective in predicting balance, functional mobility and falls in older people as more expensive and time-consuming muscle mass-based measures. These findings imply that functional terms such as muscle weakness or motor impairment are preferable to sarcopenia.